Judicial Governance in Administrative Oversight: A Comparative Study of the Indonesian Constitutional Court and the Dutch Raad van State - Mukmin Muhammad; Syamsiah Syamsiah (SEAN Institute, 2026)
This study examines how constitutional and administrative courts shape judicial governance in supervising administrative power through a comparative analysis of the Indonesian Constitutional Court and the Dutch Raad van State. The research is motivated by the increasing expansion of administrative discretion, which requires stronger judicial mechanisms to ensure accountability, legality, and proportionality in public administration. Employing a qualitative doctrinal approach, this study analyzes twelve Constitutional Court decisions and ten landmark decisions of the Dutch Raad van State using comparative legal analysis. The findings reveal three principal dimensions of judicial governance. First, accountability review emphasizes constitutional responsibility for governmental decision-making and legislative processes. Second, proportionality review strengthens judicial control over administrative discretion by balancing public interests and individual rights. Third, legality review ensures that administrative authorities remain bound by constitutional principles and statutory mandates. The Dutch experience demonstrates a mature proportionality doctrine that evolved after the childcare benefits scandal, while the Indonesian Constitutional Court increasingly integrates constitutional accountability into administrative governance through conditional unconstitutional decisions and procedural constitutional review. Based on these findings, the study develops a Judicial Governance Model consisting of Accountability Review, Proportionality Review, and Legality Review as an integrated framework for democratic administrative oversight. The model contributes theoretically to administrative governance literature by bridging constitutional adjudication and administrative justice within a unified governance perspective.